2018
DOI: 10.3390/nu10081068
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Fatty Acid Intake and Status, Desaturase Activities, and FADS Gene Polymorphism in Centrally Obese Postmenopausal Polish Women

Abstract: Fatty acid (FA) status is associated with the risk of several diet-related diseases. Since postmenopausal women are at increased risk of cardiometabolic disturbances, determinants of FA metabolism should be fully understood in this group. We hypothesize that FA metabolism in postmenopausal Polish women may depend on current macronutrient intake and on fatty acid desaturase (FADS) gene polymorphism. One-hundred-and-twenty-eight postmenopausal women with central obesity were recruited to the study and their diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…There were studies that show that the enzyme encoded by FADS2 gene can convert LA and ALA into GLA and STD, respectively [30]. FADS2 gene polymorphism is associated with MetS, and NAFLD as a component of Mets is associated with increased risk of CAD [6, 3133]. Therefore, we speculate that the FADS2 gene polymorphism is associated with NAFLD and CAD.…”
Section: Discussionmentioning
confidence: 80%
“…There were studies that show that the enzyme encoded by FADS2 gene can convert LA and ALA into GLA and STD, respectively [30]. FADS2 gene polymorphism is associated with MetS, and NAFLD as a component of Mets is associated with increased risk of CAD [6, 3133]. Therefore, we speculate that the FADS2 gene polymorphism is associated with NAFLD and CAD.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, the associations between rs174547 in FADS1 and seven types of FA, D5D activity and D6D activity were assessed based on the pooled results from eleven papers (12,16,(18)(19)(20)(21)(22)(23)(24)(25)(26) . The results demonstrated that minor C allele carriers of rs174547 had higher LA and ALA levels, lower GLA and AA levels, and lower D5D and D6D activities than the TT genotype group.…”
Section: Discussionmentioning
confidence: 99%
“…rs174547 is a functional variant associated with decreased FADS1 expression in the human liver (17) . Several studies (12,16,(18)(19)(20)(21)(22)(23)(24)(25)(26) have focused on this variant and its association with PUFA levels. Among the tag SNP of FADS1 gene, rs174547 tags up to seven other SNP in an 11-kb genomic region of FADS1 with a linkage disequilibrium threshold of R 2 > 0•8 (16) .…”
mentioning
confidence: 99%
“…The serum was stored at −80 °C. Fatty acids were extracted with the modified Folch method [ 39 , 41 ], briefly Folch reagent (2:1 chloroform:methanol), for lipid extraction from cells; butylated hydroxytoluene as an antioxidant and internal standard: deuterated myristic acid-d 27 (d 27 C14:0) in chloroform was added to the weighed samples and centrifuged. Extraction of the fat for the determination of sterols was performed in the same manner, except that the internal standard 5α-cholestane was added to the samples instead of the above-mentioned standard.…”
Section: Methodsmentioning
confidence: 99%
“…Fatty acid content was calculated by comparing the area of individual peaks with the area of the peak of the internal standard and recalculated on the basis of the sample weight Response factors (FID) for individual fatty acids compared to internal standards were taken as unity. The concentration of fatty acids was expressed quantitatively [41]. The content of sterols and stanols was determined according to the AOCS Official Method Ch 6-91 [43].…”
Section: Analysis Of Fatty Acid Composition Of Serummentioning
confidence: 99%